Inpatient Costs for Patients with Inflammatory Bowel Disease and Acute Pancreatitis. Issue 5 (25th February 2016) - Alexoff, Aimee; Roginsky, Grigory; Zhou, Ying; Kalenda, Michelle; Minuskin, Kelly; Ehrenpreis, Eli D.
Abstract: Background: Inflammatory bowel disease (IBD) is associated with an increased risk of acute pancreatitis (AP). Our group examined differences in length of stay and costs for patients with IBD hospitalized for AP and the general population. Methods: Using the National Inpatient Sample, we examined all admissions during 2005 to 2011 with a primary diagnosis of AP and codiagnosis of IBD. Continuous variables were reported as mean ± SD and compared between IBD and controls. To compare the outcomes of interest, we conducted a 1:3 propensity score matching using a greedy algorithm based on age, gender, race, number of comorbidities, procedures, insurance, income quartiles, hospital bed size, hospital location, and teaching status. Statistical analyses were performed on SAS 9.3 (Cary, NC). Results: There were 4291 hospitalizations of patients with IBD and AP over the 7-year period and 379, 627 hospitalizations of patients without IBD and with AP. More patients with Crohn's disease developed AP than patients with ulcerative colitis (2145 versus 1219). The length of stay and costs for patients with AP and IBD were significantly higher than controls (5.7 days versus 4.9 days, P < 0.0001 and $29, 724.89 versus $27, 916.76, P < 0.0001). The percentage of patients with alcohol abuse was lower in patients with IBD than that of controls (11.8% versus 21.7%, P < 0.0001). However, the percentage of patients with IBD who were drug abusers was higher than controls (5.8% versus 4.3%, P < 0.0005). Conclusions: Our study suggests that a codiagnosis of Crohn's disease or ulcerative colitis incurs a greater economic burden in patients with AP.